Safety and Efficacy of Anticoagulation in Patients with Cirrhosis: A Meta-Analysis - Huan Chen; Jiaming Lei; Sicheng Liang; Gang Luo; Mingming Deng; Muhan Lü (Canadian Journal of Gastroenterology and Hepatology)
Background and Aims. Portal vein thrombosis is a serious adverse event that occurs during liver cirrhosis. We performed a meta-analysis to evaluate the safety and efficacy of anticoagulant therapy and prophylactic anticoagulant therapy in cirrhosis patients with (/without) portal vein thrombosis. Methods. Eligible comparative studies were identified by searching the following electronic databases: PubMed, Embase, Cochrane Library, Web of Science, and CNKI. A meta-analysis was performed to calculate odds ratios and 95% confidence intervals using fixed-effects models. Recanalization and thrombus progression were defined as the primary outcomes. Secondary outcomes included adverse events and death mortality. Results. A total of 3479 patients were included in this analysis. Compared with the control group, the recanalization rate in the anticoagulant therapy group was increased P<0.00001 in patients with cirrhosis and portal vein thrombosis without increasing adverse events. Multiple use of enoxaparin in small doses is safer than single large doses P=0.004. Direct oral anticoagulants are more effective P<0.00001 and safer than traditional anticoagulants. Prophylactic anticoagulant therapy can effectively prevent portal vein thrombosis formation P<0.00001. Conclusions. Anticoagulation therapy can treat or prevent portal vein thrombosis in patients with liver cirrhosis and is a relatively safe treatment.